Naturally a female labour?: Feminist discussions in the Southern Cone (1970-1990) (Tempo e Argumento, 2011)
The relation between women and housework, even though affirmed by the feminisms and the gender studies as culturally built, has its main contribution in the naturalization of these functions. In this article I have the purpose of writing a history of the discussion about the naturalization of the housework in the Second-wave feminisms of Southern Cone, using as source the printed production of these feminisms, mostly periodicals. It is important to note that the specified period is given by the sources I have used and, through them, I intend to settle this discussion starting from a historiographic perspective inserted in the feminist and gender studies, with the support of bibliography contemporary to the utilized documents and current bibliography.
Keywords: housework; history of feminism; second-wave feminism; southern cone; feminist press